2013
DOI: 10.1021/bi4005478
|View full text |Cite
|
Sign up to set email alerts
|

Computational Studies of the Cholesterol Transport between NPC2 and the N-Terminal Domain of NPC1 (NPC1(NTD))

Abstract: The transport of cholesterol from NPC2 to NPC1 is essential for the maintenance of cholesterol homeostasis in late endosomes. On the basis of a rigid docking model of the crystal structures of the N-terminal cholesterol binding domain of NPC1(NTD) and the soluble NPC2 protein, models of the NPC1(NTD)-NPC2-cholesterol complexes at the beginning and the end of the transport as well as the unligated NPC1(NTD)-NPC2 complex were studied using 86 ns MD simulations. Significant differences in the cholesterol binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(63 citation statements)
references
References 52 publications
(118 reference statements)
5
58
0
Order By: Relevance
“…The proximity and interaction of these pockets could trigger sterol transfer from NPC2 to NPC1's NTD, consistent with biochemical data that suggest that NPC2-NPC1 interaction catalyzes this process (13). It is important to note that NPC2 binding to NPC1 may trigger a conformational change(s) that reorients NPC1 NTD into a more planar configuration in relation to NPC2 to accomplish actual cholesterol transfer, as previously modeled (19,21). Alanine scanning mutagenesis identified three NPC2 residues, M79, V81, and V83, as being needed for cholesterol transfer from NPC2 to NPC1's NTD, but not for cholesterol binding; P120 influenced cholesterol binding (19).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The proximity and interaction of these pockets could trigger sterol transfer from NPC2 to NPC1's NTD, consistent with biochemical data that suggest that NPC2-NPC1 interaction catalyzes this process (13). It is important to note that NPC2 binding to NPC1 may trigger a conformational change(s) that reorients NPC1 NTD into a more planar configuration in relation to NPC2 to accomplish actual cholesterol transfer, as previously modeled (19,21). Alanine scanning mutagenesis identified three NPC2 residues, M79, V81, and V83, as being needed for cholesterol transfer from NPC2 to NPC1's NTD, but not for cholesterol binding; P120 influenced cholesterol binding (19).…”
Section: Discussionsupporting
confidence: 82%
“…In this state, the two cholesterol-binding pockets can be aligned to form a cholesterol-transfer tunnel (Fig. 5B), although the angle of this interaction is more acute than previous proposals (19,21). The proximity and interaction of these pockets could trigger sterol transfer from NPC2 to NPC1's NTD, consistent with biochemical data that suggest that NPC2-NPC1 interaction catalyzes this process (13).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Superposition of these crystal structures onto the previously modeled 6,14 NPC1-NPC2 cholesterol complex (Figure 6a) showed that the isooctyl tail of cholesterol in NPC1 and the hydroxyl head of cholesterol sulfate in NPC2 are separated by approximately 5 Å. In an extended conformation, this distance corresponds to five linker atoms.…”
Section: Resultsmentioning
confidence: 92%
“…12 The precise details of the interaction of NPC1 and NPC2 proteins during the critical cholesterol hand-off have only begun to be elucidated, 13 and computational modeling has also been used to probe this interaction. 14,15 Finally, how the NPC1-bound cholesterol is transported across the lysosome membrane and whether a cytosolically-oriented protein drives the transfer equilibrium by receiving cholesterol from NPC1 is not yet known.…”
Section: Introductionmentioning
confidence: 99%